2016
DOI: 10.1097/nmd.0000000000000484
|View full text |Cite
|
Sign up to set email alerts
|

Religion as a Risk Factor for Suicide Attempt and Suicide Ideation Among Depressed Patients

Abstract: We aimed to examine the relationship between religion and suicide attempt and ideation. 321 depressed patients were recruited from mood-disorder research studies at the New York State Psychiatric Institute. Participants were interviewed using the SCID, Columbia University Suicide History form, Scale for Suicide Ideation, and Reasons for Living Inventory. Participants were asked about their religious affiliation, importance of religion, and religious service attendance. We found that past suicide attempts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 59 publications
3
32
0
2
Order By: Relevance
“…This is particularly relevant for Judeo-Christian related religions due in part to the conceptualization of several mental illness symptoms as sins (i.e. suicide attempts or drug abuse) [47]. In addition, it can also impact PWSMI's treatment seeking behaviors through the belief that healthcare is not needed in light of their religion [40].…”
Section: Stigma Mental Illness and Culturementioning
confidence: 99%
“…This is particularly relevant for Judeo-Christian related religions due in part to the conceptualization of several mental illness symptoms as sins (i.e. suicide attempts or drug abuse) [47]. In addition, it can also impact PWSMI's treatment seeking behaviors through the belief that healthcare is not needed in light of their religion [40].…”
Section: Stigma Mental Illness and Culturementioning
confidence: 99%
“…However, not all studies on religiosity and suicidality have found a negative association. Specifically, although several authors have found that religiosity is a protective factor against suicidality , other authors have found either a non‐significant or a positive association . For example, the two largest studies on this topic have yielded conflicting results .…”
Section: Introductionmentioning
confidence: 99%
“…Our result showing that males for whom religion/spirituality was 'extremely important' had increased odds of having chronic SI compared to no SI seems to run counter to the dictum that religion/spirituality protect against suicidality. Nonetheless, according to Lawrence et al (2016aLawrence et al ( , 2016b, aspects of religiosity, such as affiliation and service attendance, may protect against suicide attempt but not necessarily against suicidal ideation. For instance, religious or spiritual beliefs may prevent some at-risk individuals from acting out their suicidal tendencies.…”
Section: Discussionmentioning
confidence: 99%